Stock Market Volatility Analysis During the Global Financial Crisis: Literature Review - Biu*, Gilberth Sontanan; Kusuma, Prambudi Katon (Universitas Syiah Kuala, 2023)
This study presents a literature review on the analysis of stock market volatility during the global financial crisis. The global financial crisis in 2008 was one of the most significant events in modern financial history that had a major impact on stock markets around the world. The main objective of this study is to summarize the main findings in the literature related to stock market volatility during the global financial crisis, as well as to present a deeper understanding of the factors that influence stock market volatility in the context of financial crises. In this literature analysis, we explore various theories and models used to understand stock market volatility, including ARCH/GARCH models, market efficiency, behavioral finance theory, and behavioral economics theory. We also explore literature that examines the impact of macroeconomic factors, monetary policy, investor sentiment, and other factors on stock market volatility during the global financial crisis. The results show that the global financial crisis had a significant impact on stock market volatility, with significant spikes in volatility during the period. Factors such as economic uncertainty, changes in monetary policy, and negative investor sentiment all contributed to the increase in stock market volatility. In addition, the research also highlights the importance of the interaction between micro and macroeconomic factors in shaping stock market volatility during the global financial crisis. This research provides valuable insights into the complexity of stock market volatility during the global financial crisis and provides a foundation for further research in understanding market dynamics during similar periods of financial crisis in the future. With a better understanding of the factors that influence stock market volatility, investors and policymakers can take better measures in managing risk and maintaining financial market stability.